Exploring strategies of career planning and development in the hospitality industry: A case study of managerial employees of Maldives island resorts - Ahmed Faris (Prince of Songkla University, 2016)
Thesis (M.B.A., Hospitality and Tourism Management)--Prince of Songkla University, 2010